Shariah Risk Management Practices in Malaysian Islamic Banks - Mohd Ariffin, Noraini (International Journal of Economics, Management and Accounting, 2022)
Shariah compliance in Islamic banks is important to provide confidence and assurance to the public, as well as improve the credibility of Islamic banking operations in the financial market. Islamic banks can be potentially exposed to the Shariah non-compliance risk if the operations and business activities do not adhere to Shariah principles. In light of this, Shariah risk management is very important in Islamic banks. The Central Bank of Malaysia (Bank Negara Malaysia) requires Islamic banks to incorporate Shariah risk management practices as part of the necessary Shariah functions in Islamic banking institutions. This is part of the Shariah Governance Policy Document, issued by Bank Negara Malaysia in 2019. The Shariah risk management function is to systematically identify, measure, monitor and control Shariah non-compliance risk and mitigate any potential non-compliance events. This is consistent with the other two Shariah control functions, which involve Shariah review and Shariah audit. Within this setting, the present study is conducted to examine the existing Shariah risk management practices in selected Islamic banks in Malaysia as well as providing recommendations on the best Shariah risk management practices. Institutional theory and contingency theory are used in this study. Interviews with several key officers from selected Islamic banks were conducted to obtain their views on Shariah risk management practices since they are involved directly in managing Shariah non-compliance risks in their respective banks. Findings showed that existing Shariah risk management practices in Islamic banks are similar to those of conventional banking institutions in terms of risk identification, risk measurement, risk monitoring and controlling, and risk reporting. Nonetheless, for Shariah risk management, the focus was on managing Shariah non-compliance since Shariah requirements need to be adhered to at all times. All of the interviewees from the selected banks agreed that the risk identification stage is the most crucial in Shariah risk management. The implication of the study is to have a Shariah risk management framework for Islamic banks so that practices are consistently used. In addition, this can assist the Shariah audit in conducting risk-based audit. Bank Negara Malaysia should also play a role by issuing guidelines on Shariah risk management as a guidance for Islamic banks in Malaysia.